2020
DOI: 10.1002/app.50305
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene fluoride)/thermoplastic polyurethane flexible and 3D printable conductive composites

Abstract: This work focus on the development of polymeric blends to produce multifunctional materials for 3D printing with enhanced electrical and mechanical properties. In this context, flexible and highly conductive materials comprising poly(vinylidene fluoride)/thermoplastic polyurethane (PVDF/TPU) filled with carbon black‐polypyrrole (CB‐PPy) were prepared by compression molding, filament extrusion and fused filament fabrication. In order to achieve an optimal compromise between electrical conductivity, mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 51 publications
(139 reference statements)
3
26
0
Order By: Relevance
“…31,32 Furthermore, only a few studies report on the use of polymeric blends to control properties and improve printability of composite filaments for FFF. 24,33 Our previous work focused on the development of flexible and highly conductive filaments composed of polymeric blends of poly(vinylidene fluoride) (PVDF) and TPU in order to achieve the best relationship between mechanical properties, electrical conductivity and printability. Two polymeric blends composed of PVDF/TPU were used as matrix to prepared compression molded and 3D printed composites comprising carbon black-polypyrrole (CB-PPy) as conductive filler.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 Furthermore, only a few studies report on the use of polymeric blends to control properties and improve printability of composite filaments for FFF. 24,33 Our previous work focused on the development of flexible and highly conductive filaments composed of polymeric blends of poly(vinylidene fluoride) (PVDF) and TPU in order to achieve the best relationship between mechanical properties, electrical conductivity and printability. Two polymeric blends composed of PVDF/TPU were used as matrix to prepared compression molded and 3D printed composites comprising carbon black-polypyrrole (CB-PPy) as conductive filler.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the investigated PVDF/ TPU/CB-PPy composites can be potentially used for technological applications that requires electrical conductivity. 33 In this context, the present study focuses on the use of the previous developed materials as flexible pressure sensors. Due to the good combination of flexibility, printability and electrical properties, the composites prepared in the mentioned research comprising PVDF/TPU 50/50 wt% as matrix are further characterized in this paper and their piezoresistive response are investigated to evaluate its application as piezoresistive flexible pressure sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic solvents can be toxic and harmful for the environment and their disposal can be rather costly. Other techniques that are also implemented, such as extrusion or compression molding [5][6][7], typically use high temperatures that can degrade some polymers. Moreover, if polymers need to be heated to get impregnated with bioactive compounds, which, in most cases, are thermolabile substances, such substances may get damaged because of the high processing temperatures [8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this issue may be overcome by incorporating appropriate Zn(WO 4 ) 2 loadings to balance dimensional tolerances without sacrificing the mechanical properties. A blend of PVDF/thermoplastic polyurethane (TPU) filled with carbon black-polypyrrole (CB-PPy) filament was used by Bertolini et al [ 80 ] in fabricating a flexible and FDM printable conductive composite. The optimal printability, electrical, and mechanical properties of the resulting composites were achieved by optimizing the blend and filler compositions.…”
Section: Overview Of Am Techniquesmentioning
confidence: 99%